Atomic oxygen ion retrieval from 630.0 nm airglow during geomagnetically quiet periods: a mid-latitude case study near Irkutsk - Y. Duann; L. C. Chang; Y.-C. Chiu; C. C. J. H. Salinas; A. V. Dmitriev; K. G. Ratovsky; I. V. Medvedeva; R. Vasilyev; A. V. Mikhalev; J. Y. Liu; C. H. Lin; T.-W. Fang (Geoscience Letters)
Abstract This study develops and validates three photochemical inversion models to retrieve atomic oxygen ion density ([O+]) profiles from 630.0 nm airglow emissions in the mid-latitude ionosphere during geomagnetically quiet period. Using passive ground-based instruments and empirical models, the models were tested and compared against electron density data from FORMOSAT-3/COSMIC (F3/C) and DPS-4 digisonde at Irkutsk. Among the models, Inversion Model 3 showed the strongest agreement with observations, particularly in capturing seasonal variations such as the June–July peak and a secondary March–April peak, which were absent in IRI-2012 predictions. These results highlight the potential of Inversion Model 3 for accurate [O+] retrieval, offering a novel approach for monitoring ionospheric variability using passive photometric observations.